PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN SPINNER SAINS TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV SDK ST. YOSEPH 3 NAIKOTEN - Olifa Sriyati Teftae; Cornelia Amanda Naitili; Yulsi Marseline Nitte (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to improve student learning outcomes in the Science subject in grade IV of SDK St. Yoseph 3 Naikoten, Kupang City, through the application of science spinner media. This study is a type of quantitative research using quasi-experiments conducted with 1 class and divided into 2 groups, namely the control group and the experimental group. The subjects of this study were 27 grade IV students. The instruments in the study were observation, tests and documentation. Validity test is calculated using Microsoft Excel 2010 with the results of 19 valid questions and 1 invalid question, reliability test is calculated using Microsoft Excel 2010 with a value of r = 98 with a very high criterion conclusion, the level of difficulty test is calculated using Microsoft Excel 2010 with a conclusion of 19 medium numbers and 1 difficult number and the test of the discriminating power of questions with a conclusion of 19 very good numbers and 1 bad number, hypothesis test t-test with SPSS 16 With the provision of Sig (2 tailed) t-test for equal variances assumed at 0.000, then a value <0.05 means Ho is rejected and Ha is accepted. The results of this study indicate an increase in student learning outcomes that can be seen from the average learning outcomes in the control class posttest, namely 63.84 and the experimental class 87.14, from these results it shows that the learning outcomes of the control class are lower than the experimental class. Furthermore, based on the results of data analysis using the hypothesis test T-Tests (Independent Samples Tests) above, at the sig. (2-tailed) t-test for Equal variances assumed of 0.000, the significance value <0.05 means that Ho is rejected or Ha is accepted so that it can be concluded that there is a significant influence of science spinner learning media on the science learning outcomes of fourth grade students of SDK St. Yoseph 3 Naikoten, Kupang City.